2010
DOI: 10.1007/s11099-010-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sun- and shade-adapted populations of an endangered plant Primulina tabacum Hance

Abstract: Primulina tabacum Hance is an endangered perennial herb distributed in calcium-rich and nitrogen-limited soil of the karst limestone areas in southern China. The morphological, ultrastructural, and physiological traits were determined for P. tabacum populations growing in three different environment conditions: twilight zone of a cave (site TZ, extremely low light intensity), at a cave entrance (site EZ, low light intensity), and in an open area (site OA, high light intensity). At site OA, P. tabacum plants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…These findings are consistent with the rich literature on adaptations of equilibrium (or static) photosynthetic light responses to contrasting light regimes [5,8,10,11,[15][16][17][18][19][20][21][22][23][24][25][26]. Such adaptations have only rarely been studied in large numbers of closely related taxa (Euphorbia and Scaevola [27][28][29]; Acer [30][31][32]; Psychotria [33]; Sonchus alliance [34]), and, outside the Hawaiian lobeliads, never for plants whose distributions along natural light gradients have been quantified and whose phylogenetic relationships with each other are well characterized.…”
supporting
confidence: 91%
“…These findings are consistent with the rich literature on adaptations of equilibrium (or static) photosynthetic light responses to contrasting light regimes [5,8,10,11,[15][16][17][18][19][20][21][22][23][24][25][26]. Such adaptations have only rarely been studied in large numbers of closely related taxa (Euphorbia and Scaevola [27][28][29]; Acer [30][31][32]; Psychotria [33]; Sonchus alliance [34]), and, outside the Hawaiian lobeliads, never for plants whose distributions along natural light gradients have been quantified and whose phylogenetic relationships with each other are well characterized.…”
supporting
confidence: 91%
“…60 species (see Taxonomic Treatment) mainly distributed in Guangxi, inhabit the ‘twilight zone’ (Poulson and White1969) of limestone caves and cave-like microhabitats such as shaded fissures and crevices abundantly occurring throughout the Sino-Vietnamese limestone karst region (Sweeting1978; Schindler1982; Xu1995; Zhu2007). Such cave-like microhabitats, characterized by constant temperature, high humidity, and indirect and low light (Liang et al2010), function as shelters on the limestone bedrock characterized by highly alkaline conditions, thin soil layers, and severe desiccation due to high porosity (Clements et al2006). In addition to Begonia , these cave-like microhabitats are also inhabited by several species-rich, calciphilous herbaceous plant groups such as Aspidistra Ker Gawl.…”
Section: Discussionmentioning
confidence: 99%
“…, 2001; Panditharathna et al. , 2008; Liang et al. , 2010), may also play a role in thermal tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the large cladodes of American desert cacti, which can have time constants of several hours because of their great thermal mass (Nobel, 1988). More subtle changes in the thermal mass of much smaller plant parts, for example through increases in leaf thickness towards the outer canopy (Terashima et al, 2001;Panditharathna et al, 2008;Liang et al, 2010), may also play a role in thermal tolerance. In one of the few studies investigating this concept, Ball et al (1988) showed that the large heat capacities of thick mangrove leaves at the top of a plant crown damp fluctuations in leaf temperature relative to thinner leaves, thereby reducing excursions into the temperature range unfavourable for photosynthesis.…”
Section: Introductionmentioning
confidence: 99%